2016
DOI: 10.1002/smj.2551
|View full text |Cite
|
Sign up to set email alerts
|

Corporate divestitures and family control

Abstract: This paper investigates the relationship between divestitures and firm value in family firms. Using handcollected data on a sample of over 30,000 firm-year observations, we find that family firms are less likely than non-family firms to undertake divestitures, especially when these companies are managed by family rather than non-family-CEOs. However, we then establish that the divestitures undertaken by family firms, predominantly those run by family-CEOs, are associated with higher post-divestiture performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…By contrast, the latter managers and directors are more likely to be incentivised to pursue growth opportunities and maximize the efficiency of the operation, because their reputation, personal needs, satisfaction and benefits are closely linked to performance and success of the business. Rather interestingly, Feldman et al (2013) argue that family owned businesses will venture into a growth opportunity only if it is greater than the value it creates for non-family owned 20 businesses as they have other operational motives rather than building up share values. For instance, as Wennberg et al (2011) point out that if the intention of the family owners is to pass on to the next generation, then they would be very risk adverse in prioritizing long term stability and survival over growth.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the latter managers and directors are more likely to be incentivised to pursue growth opportunities and maximize the efficiency of the operation, because their reputation, personal needs, satisfaction and benefits are closely linked to performance and success of the business. Rather interestingly, Feldman et al (2013) argue that family owned businesses will venture into a growth opportunity only if it is greater than the value it creates for non-family owned 20 businesses as they have other operational motives rather than building up share values. For instance, as Wennberg et al (2011) point out that if the intention of the family owners is to pass on to the next generation, then they would be very risk adverse in prioritizing long term stability and survival over growth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, scholars have suggested that family firms are good at continuous, less disruptive innovation in their current niches (Zellweger et al 2010). When family firms engage in strategic change, such as divestitures (Feldman et al 2016), diversification (Adhikari and Sutton 2016) or acquisitions (André et al 2014;Caprio et al 2011), they are often more successful than their nonfamily firm counterparts.…”
Section: Familiness and Strategic Changementioning
confidence: 99%
“…Research has shown the distractive effects of familiness on strategic change by studying different types of strategic change. For example, family ownership and family involvement in management decrease the likelihood of divesting assets (Caprio K et al 2011;Chi-Nien and Xiaowei 2008;DeTienne and Chirico 2013;Feldman et al 2016) or diversifying (Aktas et al 2016;Anderson and Reeb 2003b;Gomez-Mejia et al 2010;Schmid et al 2015). One of the most prominent types of strategic change that has received widespread attention from family firm researchers is technology adoption and innovation.…”
Section: Familiness and Strategic Changementioning
confidence: 99%
“…From an internal stakeholder perspective, although strides have been made in deciphering the influence of investors, directors, and managers (Brauer and Wiersema 2012;Feldman 2015b, c;Feldman et al 2015), these studies represent only the beginning of an important research trajectory. Indeed, with the ongoing rise in activist investors taking a vocal part in encouraging and leading divestitures, this evolving research stream is notably vibrant.…”
Section: Future Research Directionsmentioning
confidence: 99%